LITERATUR REVIEW: EVALUASI PEMANFAATAN DATA WAREHOUSE DALAM TRANSFORMASI WAKTU - Azzahra, Afifah; Aditya, Putra; Wijaya, Andri (LPPM Universitas Bina Bangsa, 2023)
In today's digital era, data has a very important role for various organizations and industrial sectors. One of the technological solutions used to manage and analyze large amounts of data is a data warehouse. Covers the time period from 2018 to 2022. The research results show that the role of data warehouses is increasingly vital in various domains, including television editorial, sales, administration, education, health, agriculture and other sectors. There is potential for further research involving more Case studies in less explored areas, such as the environment, energy or transport